Charleston syllabus: readings on race, racism, and racial violence - Williams, Chad Louis; Williams, Kidada E.; Blain, Keisha N.; Williams, Chad Louis (The University of Georgia Press, 2016)
Part I. Slavery, survival, and community building / Kidada E. Williams -- "An address to the slaves of the United States" / Henry Highland Garnet -- From life and adventures of Charles Ball / Charles Ball -- From incidents in the life of a slave girl / Harriet Jacobs -- "Roll Jordan roll" / adapted by Nicholas Britell -- "I've been in the storm so long" -- "Before Charleston's church shooting, a long history of attacks" / Douglas R. Egerton -- "The first attack on Charleston's AME Church" / Maurie McInnis -- From "sweet dreams of freedom': freedwomen's reconstruction of life and labor in lowcountry South Carolina" / Leslie Schwalm -- From soul by soul: life inside the antebellum slave market / Walter Johnson -- From saltwater slavery: a middle passage from Africa to American diaspora / Stephanie E. Smallwood -- From in the shadow of slavery: African Americans in New York City, 1626-1863 / Leslie M. Harris -- Part II. Religious life, spirituality, and racial identity / Keisha N. Blain -- From religious experience and journal of Mrs. Jarena Lee, giving an account of her call to preach the gospel / Jarena Lee -- "Amazing grace" / John Newton -- "Love and terror in the Black church" / Michael Eric Dyson -- "The long and proud history of Charleston's AME Church" / Manisha Sinha -- "The condition of Black life is one of mourning" / Claudia Rankine -- From African American religion: a very short introduction / Eddie S. Glaude -- From "bitter herbs and a lock of hair: recollections of Africa in slave narratives of the Garrisonian era" / Jermaine O. Archer -- From Islam in Black America: identity, liberation, and difference in African American Islamic thought / Edward Curtis -- From God's long summer: stories of faith and civil rights / Charles Marsh -- From songs of Zion: the African Methodist Episcopal Church in the United States and South Africa / James Campbell -- Part III. The Civil War and Reconstruction in history and memory / Kidada E. Williams -- "The Civil Rights Bill": extracts from a speech delivered in the House of Representatives / Robert Brown Elliot -- "Declaration of the immediate causes which induce and justify the secession of South Carolina from the federal union" -- From "The Constitution of the Confederate States" / with annotations by Stephanie McCurry -- "Corner stone speech" / Alexander H. Stephens -- "No more auction block for me" / Gustavus D. Pike -- From "A second Haitian revolution: John Brown, Toussaint Louverture, and the making of the American Civil War" / Matthew Clavin -- From Black over White: Negro political leadership in South Carolina during Reconstruction / Thomas C. Holt -- From to joy my freedom: southern Black womens' lives and labors after the Civil War / Tera W. Hunter -- From Confederate reckoning: power and politics in the Civil War south / Stephanie McCurry -- From terror in the heart of freedom: citizenship, sexual violence, and the meaning of race in the post-emancipation south / Hannah Rosen -- Part IV. Jim Crow, racial politics, and global White supremacy / Kidada E. Williams -- From Plessy v. Ferguson / Supreme Court of the United States (163 U.S. 537) -- From "Declaration of the rights of the Negro peoples of the world: the principles of the Universal Negro Improvement Association" / Marcus Garvey and the UNIA -- "Call to the march" / Asa Philip Randolph -- From "The souls of White folk" / W.E.B. Du Bois -- From a red record / Ida B. Wells-Barnett -- "If we must die" / Claude McKay -- "Strange fruit" / Abel Meeropol and Billie Holliday -- "Rhodesian flag, Confederate flag: roof and the legacies of racial hate" / Benjamin Foldy -- From southern horrors: women and the politics of rape and lynching / Crystal N. Feimster -- From "We are not what we seem': rethinking Black working-class opposition in the Jim Crow south" / Robin D.G. Kelley -- From "to speak when and where I can': African American women's political activism in South Carolina in the 1940s and 1950s" / Cherisse Jones-Branch -- From the possessive investment in whiteness: how White people profit from identity politics / George Lipsitz -- "Blackness beyond boundaries': navigating the political economies of global inequality" / Manning Marable -- Part V. Civil rights and Black power / Chad Williams -- "Testimony before the Credentials Committee, Democratic National Convention, Atlantic City, New Jersey" / Fannie Lou Hamer -- "We shall overcome" -- "Mississippi Goddam" / Nina Simone -- "The Black agenda--Gary declaration: Black politics at the crossroads" / National Black Political Convention -- "Is it time to reevaluate the church's role in the civil rights movement?" / Robin Blake -- "More than a seat on the bus" / Danielle McGuire -- From "Joanne is you and Joanne is me': a consideration of african american women and the 'free joan little' movement, 1974-75" / Genna Rae McNeil -- From "could history repeat itself? the prospects for a second reconstruction in post-World War II South Carolina" / Robert Korstad -- From up south: civil rights and Black power in Philadelphia / Matthew Countryman -- From we will shoot back: armed resistance in the Mississippi freedom movement / Akinyele Umoja -- Part VI. Contemporary perspectives on race and racial violence / Chad Williams -- "Remarks by the president in eulogy for the honorable Reverend Clementa Pinckney, College of Charleston, Charleston, South Carolina" / Barack Obama -- "The blacker the berry" / Kendrick Lamar -- From "Investigation of the Ferguson Police Department" / United States Department of Justice Civil Rights Division -- "Speech on Walter Scott shooting" / Clementa Pinckney -- "Black bodies, White terrorism: a global reimagining of forgiveness" / Esther Armah -- "Ella taught me: shattering the myth of the leaderless movement" / Barbara Ransby -- "On the pole for freedom: Bree Newsome's politics, theory, and theology of resistance" / Brittney Cooper -- From hate thy neighbor: move in violence and the persistence of racial segregation in housing / Jeannine Bell -- From Charleston in Black and White: race and power in the south after the civil rights movement / Steve Estes -- From not even past: Barack Obama and the burden of race / Thomas Sugrue -- From "African American women, mass incarceration, and the politics of protection" / Kali Nicole Gross